Potencial para aplicação da recarga gerenciada de aquífero na bacia do Rio Gramame e parte do baixo curso do Rio Paraíba - Alves, Suênio Anderson Feliciano da Silva (2021)
The mismatch between water availability and demand has led planners and the technical scientific community to seek strategies to increase water security in watersheds that suffer from the water deficit. Thus, Managed Aquifer Recharge (MAR) represents a viable alternative that can provide greater resilience to drought with the intentional recharge of water for future use. This study aimed to recommend areas with potential for MAR with water from rivers and domestic effluents treated in the Gramame River basin and part of the lower course of the Paraíba River (BRG-BRP) from a multicriteria decision analysis in System of Geographic Information (GIS). A group decision-making approach (Hierarchical Analysis Process) generated the weights of a set of criteria and, consequently, used these weights through a weighted linear combination (WLC) in GIS to recommend such areas. A sensitivity analysis of the weight of the criteria assisted in verifying which of them influenced the suitability mapping and checking the robustness of the very high-class areas indicated by the multicriteria model of the two water sources analyzed. The spatial multicriteria model for MAR with river waters suggested that areas with high and very high potential represent 51.54% of the study area. The areas with high and very high potential for MAR with treated domestic effluent water cover 14.85% of BRG-BRP. The areas classified with very high suitability were east of the BRG-BRP, where the Alluvial Deposits are. High and very high suitability class areas also occur over the Barreiras Formation, situated on agricultural land ideal for MAR. In addition to the geology and water table depth criteria, the criteria distance from the rivers and distance from the treatment plant were sensitive to changes in weight in the models, with the least sensitive being land use and cover in both. The sensitivity analysis performed also allowed us to observe the uncertain and more robust areas, depending on the decision maker's preference for the criteria in the model. The results of this study are promising for the implementation of MAR schemes by infiltration basins with river waters and treated effluents. The maps generated in this work are helpful to aid decision making and, in practice, can compose the water management plan and be used in MAR preliminary planning stage. These maps also act as a policy guideline to improve water management in BRG-BRP.